Design and analysis of the transfer trajectory for switching landing site in emergency during the return flight of crewed lunar exploration mission. (October 2022) - Lu, Lin; Li, Haiyang; Peng, Qibo; Lv, Jiyuan
Abstract: Based on the need for switching the landing site in an emergency during the return flight of a crewed lunar exploration mission, an emergency transfer trajectory is designed and analysed. First, the problem of generating a single transfer trajectory for switching the landing site in an emergency is equivalently converted to solving a Lambert problem. Second, a calculation method based on homotopic continuation is proposed to obtain the high-fidelity solution of the Lambert problem in the complex gravitational field of the Earth-Moon system. Based on this calculation method, the design algorithm of an emergency transfer trajectory is put forward, and an improved differential evolution algorithm is used for optimization. The results of simulation examples indicate that the calculation method of the Lambert problem based on homotopic continuation has good convergence, and also verify the effectiveness and feasibility of the trajectory design algorithm proposed in this paper. Finally, extensive simulation calculations are carried out by adopting this method, and the impulsive manoeuvre characteristic of the emergency transfer trajectory is discussed. The research conclusions can provide a reference for the design of an emergency rescue scheme during the return flight of a crewed lunar exploration mission in the future. Highlights: A calculation method based on homotopic continuation is proposed to obtain a high-fidelity solution of a Lambert problem. A design algorithm is introduced to generate the optimal emergency transfer trajectory. Impulsive manoeuvres characteristic of the emergency transfer trajectory are analysed.